Donor-Derived Cell-free DNA for Personalized Immunosuppression in Renal Transplantation. Issue 1 (February 2023) - Oellerich, Michael; Budde, Klemens; Osmanodja, Bilgin; Bornemann-Kolatzki, Kirsten; Beck, Julia; Schütz, Ekkehard; Walson, Philip D.
Abstract : Background: The long-term outcomes of solid organ transplantation remain suboptimal. Therefore, appropriate biomarkers are needed in addition to immunosuppressive drugs and other traditional approaches for graft monitoring to achieve personalized immunosuppression and reduce premature graft loss. Methods: Donor-derived cell-free DNA (dd-cfDNA) is a minimally invasive biomarker of cell death due to graft injury. It can be quantified using droplet digital polymerase chain reaction and next-generation sequencing. Fractional dd-cfDNA determination can be affected by changes in recipient cfDNA, such as those caused by leukopenia or infection, leading to false-positive or false-negative results, respectively. Absolute quantification of dd-cfDNA helps in overcoming this limitation. Results: Overall, there is sufficient evidence of the clinical validity of dd-cfDNA. It detects rejection episodes early at an actionable stage and reflects the severity of graft injury without being rejection-specific. Owing to its high negative predictive value, dd-cfDNA is very useful for ruling out graft injury. Dd-cfDNA complements histological findings and can help in avoiding unnecessary biopsies. It indicates a response to rejection treatment and detects underimmunosuppression. Conclusions: Monitoring changes in dd-cfDNA over time may be helpful in adapting immunosuppression to prevent graft rejection. Moreover, serial dd-cfDNA determination may increase the effectiveness of transplant recipient surveillance and facilitate personalized immunosuppression when combined with other relevant clinical and diagnostic findings.